2017
DOI: 10.4155/fmc-2017-0082
|View full text |Cite
|
Sign up to set email alerts
|

When Will Small Molecule Lactate Dehydrogenase Inhibitors Realize Their Potential in the Cancer Clinic?

Abstract: Keywords: cancer metabolism • drug discovery • hLDH5 inhibitors • tumor glycolysis • Warburg effectReaching beyond the success in development of anticancer drugs meant to precisely focus first on one hallmark of cancer and the production of a novel type of small molecules that are selective and specific for cancer treatment. Safety is a major challenge than the efficacy in the drug development processes of small molecules, for both the academic research and pharmaceutical industries. From a metabolic assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In a murine model of Kras G12D -driven lung cancer, pharmaceutical LDHA inhibition also inhibited both tumor progression and regression [143]. Thus, optimization of GLUT1 (BAY and DRB-18) or LDHA inhibitors may offer novel therapeutic strategies for treating lung cancer [144,145,146]. The importance of this metabolic pathway for TAM effector functions has been revealed by Colegio et al who demonstrated in a murine model of Lewis lung carcinoma that lactic acid produced by tumors stabilizes HIF1α in TAMs, leading to an “M2-like” phenotype that was independent of IL-4R signaling (Figure 2, left panel) [147].…”
Section: Lung Macrophage Immunometabolism and Function In Lung Adementioning
confidence: 99%
“…In a murine model of Kras G12D -driven lung cancer, pharmaceutical LDHA inhibition also inhibited both tumor progression and regression [143]. Thus, optimization of GLUT1 (BAY and DRB-18) or LDHA inhibitors may offer novel therapeutic strategies for treating lung cancer [144,145,146]. The importance of this metabolic pathway for TAM effector functions has been revealed by Colegio et al who demonstrated in a murine model of Lewis lung carcinoma that lactic acid produced by tumors stabilizes HIF1α in TAMs, leading to an “M2-like” phenotype that was independent of IL-4R signaling (Figure 2, left panel) [147].…”
Section: Lung Macrophage Immunometabolism and Function In Lung Adementioning
confidence: 99%
“…However, although many LDHA inhibitors are under scrutiny for approval as novel anticancer drugs, none of them have been approved yet. Thus, more drug-like candidates are required to generate new LDHA inhibitors [45]. Natural compounds have been regarded as potential resources for anticancer drugs, particularly in overcoming chemoresistance as a combination therapy [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…A new class of N -hydroxy indole-based h LDHA inhibitor (NHI) was developed, which showed significant selectivity (Figure ). Although several molecules have been discovered, still there is a large chemical gap available to discover new h LDHA inhibitors as potential anticancer agents.…”
Section: Introductionmentioning
confidence: 99%